Effect of Caponization on Meat Quality and Proximate Composition of Slow-Grow ing Indbro Brown Layer Cockerels - T, Srilatha; Devatkal, Suresh K; Kishore, Karnati; Kotaiah, Talapaneni; Supriya, Ratna; Yadagiri, Chandana (Journal of Meat Science, 2026)
The intensive breeding of laying hens for egg production has led to excess production of cockerels, which are not economical for broiler production. This issue may be addressed by subjecting the cockerels to castration, fattening, and marketing them as specialty chicken meat targeting a niche market. Hence, in this study, meat quality characteristics of caponized dual-type poultry variety (Indbro) were compared with non-caponized and commercial broiler meat. Dressing percentage and breast yield were significantly (p<0.01) higher in broiler birds, whereas skin and back were significantly (p<0.05) higher in caponized birds. Protein, fat, ash content and water holding capacity of meat were (p<0.01) significantly higher in caponized birds. Cooking loss of breast and thigh meat was significantly (p<0.05) lower in caponized birds. Texture parameters did not vary significantly between the three groups. There was no significant difference between the three groups for sensory evaluation and major fatty acid composition, except for palmitoleic acid and γ-linolenic acid. Instrumental color score was significantly higher in caponized birds than in broilers. Further research into the effect of caponization on rearing economics and growth characteristics of different varieties of layers will encourage poultry layer breeders to make use of cockerels effectively for meat purposes.